Sources of Legal Regulation of Mergers, Acquisitions, Consolidations, Joint Stock Companies in Russia and Corporations in the United States - S. E. Kuzmin (Vestnik MGIMO-Universiteta)
The article outlines general characteristics of the sources of law, regulating relations associated with mergers, consolidations, acquisitions of joint stock companies in Russia and corporations in the United States respectively in the Russian legislation and the legislation of the United States and individual States. Both in Russia and in the USA there is a constitutional separation of powers between the Federal authorities and the Subjects of the Federation/States respectively. In both countries legal regulation of mergers and acquisitions of corporations is carried out first of all by a number of laws. These laws fall into three main groups: securities laws, antitrust (competition) laws and civil and joint-stock legislation in Russia and corporate laws in the US. All the three groups are federal laws in Russia, while in the US the first two are federal too, but the last one is state laws. It is necessary to highlight the important role of judicial decisions in the United States on legal regulation of mergers, acquisitions, takeovers in comparison with Russia, which is due to the differences in the legal systems of the states in question. However, although Russia is not a state of case law, such legal acts as the resolution of the Plenum of the Supreme Commercial Court will undoubtedly have an impact on law enforcement practice and, consequently, on the regulation of relevant relations. Of particular importance are the findings of the Constitutional Court, whose decisions may cancel acts or their separate provisions provided they are recognized as unconstitutional. Such acts are repealed. Decisions of courts and other bodies based on acts or their separate provisions, recognized by the Constitutional Court of the Russian Federation unconstitutional, are not subject to execution and shall be revised in accordance with the Federal law. The US case law implies existence of a hierarchy of precedents according to which decisions adopted by the higher courts are binding for cases adjudicated in lower courts. Judicial decisions have a major impact on the regulation of mergers and acquisitions of corporations, in particular, the state corporate Laws. The article analyses the main similarities and differences of sources of legal regulation of mergers, consolidations, acquisitions of joint stock companies in Russia and corporations in the United States.